(untitled) (South East Asia Journal of Public Health, 2017)
Sustainable development is one of the most discussed and desired issues for the last few decades in Bangladesh and also throughout the world. But due to various challenges it is really tough to prepare and execute a proper plan for achieving sustainable development. The objective of this study is to find out the major challenges that the urban environment has been facing in sustainable development in Dhaka city. The qualitative study was done purposively and data collection methods were 10 Key Informants Interviews (KII) and 10 Focus Group Discussions (FGDs). KII were conducted among university teachers and Government officials as well as FGDs were conducted among city duelers in Dhaka. Urbanization process providing reasonable housing and infrastructure for duelers of all financial gain categories is a nice challenge for capital of Bangladesh town. Lack of swamp, open places, public parks, land with tree cover up causes environmental degradation and also creates aesthetic discomfort is another challenge in urban areas. Surface water is becoming useless because of having extensive pumping of groundwater in capital of Bangladesh. City dwellers didn’t follow the environmental rules and pollutes the surface waters with freedom. Impenetrable population with quick urbanization, industrialization and the lack of land coming up with has created major environmental problem to establish sustainable development. In future we need to study on identify the implementation strategy to sustainable development of urban environment. South East Asia Journal of Public Health Vol.7(1) 2017: 12-16